2020
DOI: 10.3390/nu12030810
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Complementary Feeding Behaviors Predict Diet Quality in Early Childhood

Abstract: Infancy is a time of plasticity in development of taste preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
1
13
0
5
Order By: Relevance
“…A recent prospective cohort study investigated how feeding patterns during CF influence future diet quality; authors demonstrated that certain CF behaviors can predict the child's diet quality approximately 2 years later. For instance, membership in the group characterized by delayed introduction of sweets and low fruit juice intake at 1 year of age predicted higher diet quality at 3 years [124]. Consequently, in order to obtain an increased acceptance and a varied diet, caregivers should discourage innate flavor preferences of their infants by offering them healthy foods, and by not adding salt or sugar or energy-dense ingredients.…”
Section: Taste and Food Preferencesmentioning
confidence: 99%
“…A recent prospective cohort study investigated how feeding patterns during CF influence future diet quality; authors demonstrated that certain CF behaviors can predict the child's diet quality approximately 2 years later. For instance, membership in the group characterized by delayed introduction of sweets and low fruit juice intake at 1 year of age predicted higher diet quality at 3 years [124]. Consequently, in order to obtain an increased acceptance and a varied diet, caregivers should discourage innate flavor preferences of their infants by offering them healthy foods, and by not adding salt or sugar or energy-dense ingredients.…”
Section: Taste and Food Preferencesmentioning
confidence: 99%
“…The introduction of complementary foods is a crucial stage in the development and determination of infants’ health status in both the short and longer-term [ 8 , 9 , 10 , 11 ]. Furthermore, the order of introduction, variety, and repeated exposure to complementary foods are related to the development of food preferences and eating habits later in life [ 12 , 13 , 14 , 15 , 16 , 17 ]. As a result, it is not surprising that: “the way in which a child is introduced to complementary foods may have effects on the individual’s entire life” [ 11 ] (p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Offering sweet-tasting complementary foods would enhance the preference of sweet flavor and diminish acceptance of less-sweet food such as vegetables. However, appropriate taste preferences may be promoted in the first two years of life [ 50 ]. Exposure to a greater variety of flavors or foods could promote the acceptance of novel foods [ 8 ].…”
Section: Discussionmentioning
confidence: 99%